Childhood Sexual Abuse and Military Sexual Trauma Interact to Increase Suicide Risk: Results from a Nationally Representative Veteran Sample - Holliday, Ryan (Journal of interpersonal violence, 2023)
Childhood sexual abuse (CSA) and military sexual trauma (MST) are prevalent among veterans. Such exposures are associated with adverse mental-health sequelae, including elevated risk for suicidal thoughts and behaviors. Nonetheless, prior studies have largely focused upon discrete experiences of CSA or MST in circumscribed samples. In the current study, we analyzed data from a large, nationally representative sample of 4,069 US military veterans to examine main and interactive effects of CSA and MST in relation to suicidal thoughts and behaviors. After accounting for sociodemographics, psychiatric comorbidity, and trauma-related characteristics, we detected a significant interaction between MST and CSA as it related to report of past-year suicidal ideation, lifetime suicide attempt, and risk for future suicide attempt. These findings underscore the impact of sexual trauma throughout the lifespan, highlighting the continued importance of screening for trauma exposure and connecting veterans to appropriate, evidence-based treatment to decrease their risk for suicidal thoughts and behaviors.